EXPLORING STUDENTS’ PERCEPTIONS OF ARTIFICIAL INTELLIGENCE USE IN LEARNING OUTCOMES AT HIGHER EDUCATION - Nurlista Iryanti; Fenisya Anggraini (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2026)
Artificial Intelligence (AI) is increasingly integrated into higher education to support English learning through personalized and adaptive instruction. This study investigates undergraduate students' perceptions of AI and its contribution to English learning outcomes at Universitas Sriwijaya. A mixed-methods approach was employed, involving 40 students from various academic disciplines. Data were collected through questionnaires and semi-structured interviews and analyzed using thematic analysis based on the Perceiver–Target–Situation framework. The Pearson product-moment correlation analysis was also used to analyze the data. The findings indicate that students generally hold positive perceptions of AI. Familiarity with digital technology, prior experience, institutional support, peer interaction, and learning environments encouraged AI adoption. Students perceived AI as accessible, practical, and responsive to their learning needs, contributing to improvements in reading comprehension, writing performance, learning efficiency, confidence, and autonomous learning. The study concludes that positive perceptions, supported by appropriate educational contexts, facilitate the effective integration of AI in English learning and provide practical implications for AI-assisted instruction in higher education.